2020
DOI: 10.1016/j.cegh.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The cytomegalovirus seroprevalence among children in Mostar, Bosnia and Herzegovina: A hospital cross-sectional study

Abstract: Background: Cytomegalovirus (CMV) seroprevalence varies between 60% in developed countries and 100% in developing countries. The aim of this study was to assess CMV seroprevalence in representative sample of children in Bosnia and Herzegovina and to identify possible factors associated with CMV. Methods: Blood samples and surveys were collected from 253 children at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…Also, considering that most of the children from both sexes were affected, we cannot consider this data as the absolute significance and can consider it a bias. Meanwhile, a similar result has been observed by Seale et al ( 2006 ), Arora et al ( 2018 ), and Franjića et al ( 2020 ). In contrast, Adeiza et al ( 2016 ) mentioned higher rates of CMV-IgM seroprevalence in males, while Shukla et al ( 2015 ) and Bakri et al ( 2016 ) reported a higher incidence of CMV-IgG seroprevalence among females.…”
Section: Discussionsupporting
confidence: 86%
“…Also, considering that most of the children from both sexes were affected, we cannot consider this data as the absolute significance and can consider it a bias. Meanwhile, a similar result has been observed by Seale et al ( 2006 ), Arora et al ( 2018 ), and Franjića et al ( 2020 ). In contrast, Adeiza et al ( 2016 ) mentioned higher rates of CMV-IgM seroprevalence in males, while Shukla et al ( 2015 ) and Bakri et al ( 2016 ) reported a higher incidence of CMV-IgG seroprevalence among females.…”
Section: Discussionsupporting
confidence: 86%